ANALISA KEBIJAKAN PEMERINTAH DKI JAKARTA TERKAIT ANCAMAN PENGANGGURAN PASCA KENAIKAN INFLASI - Teddy Ong; Rizal Verandi; Jason Yodiputra; Angelica Vivian Christy; Shelly Elida (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2022)
Unemployment is one of the problems faced by Indonesia. This is a complex matter that must be faced because it has different patterns and is difficult to understand. The subject of our research, DKI Jakarta also has a high unemployment rate. The research method used by the research team is qualitative and quantitative techniques. The data used in this study are data on unemployment rates, inflation, government policies, and world economic and political conditions. The purpose of this study is to compare the unemployment rate data from 2019 to 2022 with the accompanying research data used.